2015
DOI: 10.1136/gutjnl-2015-310097
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma detection with Endocuff colonoscopy versus conventional colonoscopy: a multicentre randomised controlled trial

Abstract: http://www.trialregister.nl Dutch Trial Register: NTR3962.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 38 publications
7
134
2
Order By: Relevance
“…There were three studies that evaluated the cecal intubation time[16,17,21] (Table 1). The reported average cecal intubation times between the EC group were relatively similar to the standard colonoscopy group, with EC group being between 7.0 to 11.7 min compared to 8.3 to 10.7 min in the standard colonoscopy group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were three studies that evaluated the cecal intubation time[16,17,21] (Table 1). The reported average cecal intubation times between the EC group were relatively similar to the standard colonoscopy group, with EC group being between 7.0 to 11.7 min compared to 8.3 to 10.7 min in the standard colonoscopy group.…”
Section: Resultsmentioning
confidence: 99%
“…Results remained statistically significant, favoring higher adenoma detection rate in the EC group compared to the standard colonoscopy (OR = 1.42 95%CI: 1.18-1.72, I 2 = 50%, P < 0.01). Furthermore, if only indexing randomized control trials in the meta-analysis[14,15,17,19] there remains statistically significant higher adenoma detection rate in the EC compared to the standard colonoscopy group (OR = 1.33 95%CI: 1.01-1.76; I 2 = 66%, P = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…A recently published Japanese-simulated randomized study involving an anatomic colorectal model further supports the benefit of EndoCuff application for ADR improvement [78]. On the other hand, in one recently published large randomized controlled trial from the Netherlands, the use of EndoCuff was not associated with a higher ADR [79]. In that study, 1,063 patients were randomized either to EndoCuff or standard colonoscopy.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…Although all studies included both screening and diagnostic exams, an initial study showed a significant increase over a low baseline ADR with use of the Endocuff® device (35 vs. 21 %) [28]. Other investigators found no significant difference in the number of adenomas removed per patient between the Endocuff and standard exam groups, but did describe a significantly lower cecal intubation rate when using the device [29]. A third study described a higher polyp detection rate with this attachment especially in the sigmoid colon and cecum and for polyps smaller than 1 cm [30].…”
Section: Endocuff®mentioning
confidence: 93%